Prevalence, risk factors, and bacterial pathogens responsible for surgical site infection after caesarean section: a retrospective study - Pluck, Oleta; Gray, Amanda D.; Young, Latoya Z.; Rupan, Rohini A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Surgical site infection (SSI) is one of the most common complications following caesarean section (CS), with a reported incidence of 3-20%. SSIs cause a significant burden on both the mother and the healthcare system and are associated with maternal morbidity and mortality rates of up to 3%. Methods: A hospital-based retrospective study was conducted. Of 703 patient charts reviewed, 51 met the inclusion criteria. Data were extracted from medical records and analyzed using Statistical Package for the Social Sciences (SPSS). Results: The prevalence of SSI was 7.3%. Most cases (96.1%) were classified as Class I SSI, while 3.9% were Class II; no cases of organ-space infection were identified. The mean age of affected patients was 27.5 years. Obesity was present in 68.8% of the cohort. The SSI rate was 17.6% among patients with rupture of membranes (ROM) before CS. Prolonged rupture of membranes (>18 hours) occurred in 13.7% of cases, while ROM <18 hours was noted in 3.9%. Anemia and postpartum hemorrhage each accounted for 2% of associated conditions. Conclusions: At Georgetown Public Hospital, SSI following caesarean delivery remains a significant complication, with a prevalence of 7.5%. The most commonly isolated organisms were Staphylococcus aureus, followed by Escherichia coli, Klebsiella pneumoniae, and MRSA. Efforts to reduce preventable risk factors are essential to decreasing the overall burden of SSI after caesarean section.